Potential Impact of the Nonessential Energy-Dense Foods Tax on the Prevalence of Overweight and Obesity in Children: A Modeling Study - Illescas-Zárate, Daniel; Batis, Carolina; Ramírez-Silva, Ivonne; Torres-Álvarez, Rossana; Rivera, Juan A.; Barrientos-Gutiérrez, Tonatiuh (Frontiers in Public Health, 2021)
Background: Consumption of foods high in energy, sugar, fat, and salt contributes to the increase in body mass index and the prevalence of overweight and obesity in children. Mexico implemented an 8% tax to nonessential energy-dense foods (NEDF) in 2014 as part of its national strategy to reduce obesity. Objective: We estimated the potential effect of the NEDF tax on body mass index and overweight and obesity in Mexican children (6-17 y). Materials and Methods: We used the Dynamics of Childhood Growth and Obesity Model calibrated to Mexican children to simulate the potential effect of NEDF over a one-year period on body weight. NEDF consumption, weight, and height were obtained from the Mexican National Health and Nutrition Survey 2012 and used as inputs for the model. We used observational estimates of the NEDF tax effect on consumption (5.1%). Results: The tax on NEDF would lead to a reduction of 4.1 grams or 17.4 calories per day of NEDF in Mexico. After one year with taxes, mean body weight and body mass index would be 0.40 kg and 0.19 kg/m2 lower in comparison to after a year without taxes. This translates to -1.7 and -0.4 percent points in overweight and obesity, respectively. Conclusions: The use of fiscal instruments to discourage the consumption of NEDF is an effective intervention to reduce its consumption and decrease the prevalence of overweight and obesity in children.